Partisipasi Masyarakat Dalam Implementasi Kebijakan Roti 7 Lapis Dinas Pemadam Kebakaran Dan Penyelamatan Kota Surabaya - Najwa Tsaniya Anjainah; Ajeng Dwi Larasati; Dewi Rahma Aprilia Paramita; Binti Azizatun Nafi’ah (Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to analyze the level of community participation in the “Roti 7 Lapis” program (Response Time 7 Minutes of Free Fire Service) initiated by the Surabaya Fire and Rescue Department. Using a descriptive qualitative approach and Arnstein’s ladder of participation theory, the research explores citizen involvement in reporting, prevention, and early fire response. Data were collected through interviews and observations in two densely populated areas: Sidotopo Jaya and Kedung Rukem. The findings indicate that community participation has reached the